Using Superiorly Located Perforator-Based Parasacral Perforator Flaps for Reconstruction of Sacral Defects - Ercan, Alp; Ercan, Leman Damla; Yalçın, Can Ege; Morkuzu, Suat (Cerrahpaşa Medical Journal, 2024)
Objective: Despite the advances, reconstruction of the sacral region remains a challenge due to the nature of this area. Parasacral perforator flaps can be useful for small to moderate defects of the sacral area, and with the standard design, their skin paddle can overlap with the skin paddle of the superior gluteal artery perforator (SGAP) flap, forcing us to sacrifice one flap in order to use the other. In this retrospective study, we aim to present our experience with superiorly designed parasacral perforators as a single unit and their combined use with SGAP flaps. Methods: A retrospective review of 25 patients with sacral area defects reconstructed with a parasacral perforator flap or a parasacral perforator flap combined with a SGAP flap was presented in this study, and the results are discussed. Results: In our series, all flaps survived uneventfully except one. In 21 cases, a single superiorly designed parasacral perforator flap was used for coverage of a small to moderate sacral defect. In 2 cases, a combination of a parasacral flap and a SGAP flap was used simultaneously, and in 2 cases, a multi-stage approach was used with a SGAP flap in the initial stage and a parasacral flap in the second stage. We did not encounter any end resultaltering major complications, and all patients were functionally satisfied. Conclusion: With its quick learning curve and simplicity, the parasacral flap should be an essential tool in sacral reconstruction. When designed superiorly, their skin paddle would not overlap with the SGAP flap’s skin paddle, and a combination of these 2 flaps can be utilized. Cite this article as: Ercan A, Ercan LD, Yalçın CE, Morkuzu S. Using superiorly located perforator-based parasacral perforator flaps for reconstruction of sacral defects. Cerrahpaşa Med J. 2024;48(2):159-165.